2022
DOI: 10.2196/34936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the COVID-19 Pandemic on Clinical Trial Discontinuation in Anesthesiology: Cross-sectional Analysis

Abstract: Background The COVID-19 pandemic drastically altered perioperative medical practice owing to safety concerns, postponing elective or nonemergent procedures, supply chain shortages, and reallocating perioperative staff to care for patients with COVID-19. However, the impact of the pandemic on the conduct on anesthesiology clinical research is unknown. Objective The primary objective was to quantify the magnitude of the COVID-19 pandemic’s impact on anest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our study adds to the growing literature assessing the impact of COVID-19 on clinical trials registered on ClinicalTrials.gov. 17 19 , 23 We found 34 (34/2280, 1.49%) OCT discontinuations due to the pandemic. Our results are similar to other fields such as autism (15/197, 7.6%), otolaryngology (33/1777, 1.9%), anesthesia (24/823, 2.9%), and depressive disorders (5/56, 8.9%).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our study adds to the growing literature assessing the impact of COVID-19 on clinical trials registered on ClinicalTrials.gov. 17 19 , 23 We found 34 (34/2280, 1.49%) OCT discontinuations due to the pandemic. Our results are similar to other fields such as autism (15/197, 7.6%), otolaryngology (33/1777, 1.9%), anesthesia (24/823, 2.9%), and depressive disorders (5/56, 8.9%).…”
Section: Discussionmentioning
confidence: 75%
“…On June 10, 2022, ClinicalTrials.gov was accessed through the Aggregate Content of ClinicalTrials.gov (AACT), a comprehensive, relational database of ClinicalTrials.gov that is updated daily. 16 We searched the AACT using terms listed on the "Eye Diseases" page of ClinicalTrials.gov and downloaded a dataset containing every registered OCT. As performed by similar studies, [17][18][19] we used the "last update posted date" as a proxy to identify trials possibly affected by COVID-19 and to track changes in trial recruitment status. We included trials last updated between January 1, 2020 and June 8, 2022, the latest version of the database.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Te recent COVID-19 pandemic also had some drastic impact on medical practice and on the conduct of clinical research. A recent survey found that some 16.4% of anesthesiologyrelated clinical trials were discontinued within the designated data range due to COVID-19-related issues [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, starting in March 2020, the world changed, and the first wave of COVID-19 interrupted the publication of clinical trials and other works. In this systematic review, Traxler et al [41] showed that almost 20% of anaesthesiology-related clinical trials were interrupted during the first period of the pandemic.…”
Section: Clinical Areas Affected By the Coronavirus Disease 19 Outbreakmentioning
confidence: 99%